STAT3-mediated upregulation of the AIM2 DNA sensor links innate immunity with cell migration to promote epithelial tumourigenesis - Dawson, Ruby E; Deswaerte, Virginie; West, Alison C; Tang, Ke; West, Alice J; Balic, Jesse J; Gearing, Linden J; Saad, Mohamed I; Yu, Liang; Wu, Yonghui; Bhathal, Prithi S; Kumar, Beena; et al. (Gut, 2022)
ObjectiveThe absent in melanoma 2 (AIM2) cytosolic pattern recognition receptor and DNA sensor promotes the pathogenesis of autoimmune and chronic inflammatory diseases via caspase-1-containing inflammasome complexes. However, the role of AIM2 in cancer is ill-defined.DesignThe expression of AIM2 and its clinical significance was assessed in human gastric cancer (GC) patient cohorts. Genetic or therapeutic manipulation of AIM2 expression and activity was performed in the genetically engineered gp130 F/F spontaneous GC mouse model, as well as human GC cell line xenografts. The biological role and mechanism of action of AIM2 in gastric tumourigenesis, including its involvement in inflammasome activity and functional interaction with microtubule-associated end-binding protein 1 (EB1), was determined in vitro and in vivo.ResultsAIM2 expression is upregulated by interleukin-11 cytokine-mediated activation of the oncogenic latent transcription factor STAT3 in the tumour epithelium of GC mouse models and patients with GC. Genetic and therapeutic targeting of AIM2 in gp130 F/F mice suppressed tumourigenesis. Conversely, AIM2 overexpression augmented the tumour load of human GC cell line xenografts. The protumourigenic function of AIM2 was independent of inflammasome activity and inflammation. Rather, in vivo and in vitro AIM2 physically interacted with EB1 to promote epithelial cell migration and tumourigenesis. Furthermore, upregulated expression of AIM2 and EB1 in the tumour epithelium of patients with GC was independently associated with poor patient survival.ConclusionAIM2 can play a driver role in epithelial carcinogenesis by linking cytokine-STAT3 signalling, innate immunity and epithelial cell migration, independent of inflammasome activation.